ANALISIS KINERJA PEMBANGKIT LISTRIK ENERGI TERBARUKAN PADA MODEL JARINGAN LISTRIK MIKRO ARUS SEARAH - Isdawimah _; Uno Bintang Sudibyo; Eko Adhi Setiawan (Jurnal Poli-Teknologi, 2010)
This paper aims to analyze the performance of the Renewable Energy Power Plants which are consist of PLTS and PLTB 12V/100W that supplies power into DC microgrid. Before supplying the power, each power plant was tested in no-load and on-load conditions. On the DC microgrid is tested burden sharing between the PLTS and PLTB by considering the capacity of each battery. The PLTS's test results indicate that 12V 80W of solar cell that facing to the east direction on June 2010was producing electric current in the largest average number (1.954 A) and charging the 12V, 45 Ah of battery for 23 hours, faster than if faced it to the other direction. The voltage decreased occurring on PLTS and PLTB by 9.4% and 8.4% of the nominal voltage of 12V when they burdened with 80% of nominal load 100W. This happens due Load which connected into the direct current electricity micro grid, get the power supply from PLTS and PLTB on which each power plant equipped with the batteries at the same capacity 12V 45Ah. On no-load conditions, PLTS and PLTB charging the battery, while on loaded conditions, the electric current which generated by both power plants flowed into the load, with the division of electric power that supplied into the load depends on each battery’s power. Power plants with a larger charging battery supplying power greater than the power plants with a smaller charging battery. Keywords Renewable energy, microgrid, direct current, the performance ABSTRAK Paper ini bertujuan untuk menganalisis kinerja dari Pembangkit Listrik Energi Terbarukan yang terdiri dari PLTS dan PLTB 12V/80W yang akan memasok daya ke jaringan listrik mikro arus searah. Sebelum memasok daya, masing-masing pembangkit diuji dalam kondisi tanpa beban dan berbeban. Pada jaringan listrik diuji pembagian beban antara PLTS dan PLTB dengan mempertimbangkan kapasitas baterai masing-masing. Hasil pengujian PLTS menunjukkan peletakan sel surya 12V, 80W ke arah timur pada bulan Juni 2010 menghasilkan arus rata-rata terbesar (1,954A) dan mengisi baterai 12V, 45Ah selama 23 jam, lebih cepat dibanding ke arah lain. PLTS dan PLTB mengalami penurunan tegangan sebesar 9,4% dan 8,4% dari tegangan DC nominal 12V pada saat dibebani 80% dari beban nominal 100W. Hal jaringan listrik mikro arus searah memperoleh pasokan daya dari PLTS dan PLTB yang masing-masing dilengkapi baterai dengan kapasitas sama 12V, 45Ah. Pada kondisi tanpa beban, PLTS dan PLTB mengisi baterai, sedangkan pada kondisi berbeban, arus yang dihasilkan kedua pembangkit mengalir ke beban, dengan pembagian pasokan daya ke beban tergantung muatan baterai masing-masing. Pembangkit dengan baterai bermuatan besar memasok daya lebih besar dibanding pembangkit dengan baterai bermuatan lebih kecil. Kata kunci: Energi terbarukan, jaringan listrik mikro, arus searah, kinerja